Aspects of the ecology of feral goats (Capra hircus L.) in the Mahoenui giant weta reserve : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Ecology at Massey University - Stronge, Dean Charles (Massey University, 1993)
A field study of feral goats (Capra hircus) was carried out in the Mahoenui giant weta reserve, southern King Country, New Zealand, from March 1992 to February 1993. The reserve supports the main population of the undescribed Mahoenui giant weta (Deinacrida sp.). The dominant woody browse plant in the reserve, gorse (Ulex europaeus), provides protection, shelter and food for weta. The study aimed to provide information on aspects of the ecology of feral goats to better understand their role in the reserve, and to assess any possible effects on weta survival. The activities, foraging behaviour and broad diet of feral goats within the reserve were studied by means of direct observation and autopsies. Gorse was adequate for goat growth only during late spring/summer, and became a maintenance feed at other times of the year. Goat browsing has probably slowed down the rate of succession from gorse to native forest cover but not prevented it. Successional changes may be detrimental to weta survival. Ranges of male and female herds overlapped at all times of the year and animals from several ranges occupied common bedding sites during the year. Feeding (grazing and browsing) was the dominant activity of adult feral goats in the reserve. Females spent more time feeding than males. Grazing and browsing changed seasonally for both sexes, with grazing generally decreasing from autumn to summer, and browsing increasing from summer to spring. In every season females spent more time grazing than males, but males browsed more than females. Greater use of browse by the bucks may be an affect of the presence of the does. Overall goats appear to have little direct influence on weta. A possible reduction in the rate of successional change is probably the most important effect of goats in the reserve. However, in the absence of direct manipulation of the gorse, goats can not prevent succession from occurring. Monitoring systems for the feral goat population and the vegetation community structure are recommended.
Keywords: New Zealand; Feral livestock; Mahoenui Giant Weta Reserve; Feeding and feeds; Feral goats -- Environmental aspects; Feral goats -- Feeding and feeds